DEWAN PERWAKILAN RAKYAT KETUK PALU UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI JADI POLEMIK - Markus Hutapea (Yayasan Baitul Hikmah al-Zain, 2024)
This paper aims to see how the phenomenon regarding the draft revision of the Corruption Eradication Commission Act. Whether we realize it or not, some of the contents of the articles in the draft revision of this Law have indeed made the Corruption Eradication Commission withered. To prove this phenomenon, an analysis was carried out through the previous law, namely Law No. 30/2002 concerning the Corruption Eradication Commission. Because in essence a revision of the draft Act should strengthen the position of an institution. Based on data from Indonesia Corruption Watch, corruption in Indonesia is quite vulnerable. So that the Corruption Eradication Commission is indeed wanted by some elements to facilitate the actions of some elements, to become thieves in their own country. This fact did not escape the attention of the Indonesian people. Indonesian people themselves, are critical and smart enough to see, understand every policy that will be carried out by the government